PEMIKIRAN PENDIDIKAN ISLAM: TELAAH HISTORIS DAN FILOSOFIS PEMIKIRAN MUHAMMAD ABDUH - Malla, Hamlan Andi Baso (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2016)
Muhammad Abduh is known as modern and rational figure in the history and development of Islamic education. The use of reason in understanding Islamic teachings led him to have modern ideas because his thinking is deemed capable of relevancy with the times and adjust the dynamic needs of more advanced societies. He thinks about modern Islamic education as the influence of the teachings of Islam and the modern and rational character of the birth of the development of science, technology weapons and civilization which boast of the Western world as a trigger for the birth of ideas updates. With his effort to modernize the education system at the University of Al-Azhar has a great influence in the development of education reform efforts in the Islamic world, This is done as an attempt to adjust the aspect relating to mua'malah in dimensions humanity and civilization, social, political, economic, educational and interkonektif integrative done so that the values ​​of Islam socialized to Muslims through Islamic education according to the development context of its time.